2013
DOI: 10.1111/jphp.12174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage on the dissolution rate of a fast-dissolving perphenazine/β-cyclodextrin complex

Abstract: The results suggest that CD complexation may represent a suitable alternative for preparing intraorally dissolving formulations because the fast dissolution rate of the drug was maintained even though changes in the crystal structure were observed during storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Amorphous CD–drug complexes usually form when solid complex powders are prepared by cogrinding, spray drying, and freeze‐drying . Typically, amorphous pharmaceuticals exhibit greater molecular mobility and chemical reactivity than their corresponding crystalline forms, giving rise to their lower stability compared with crystalline state . Nakai et al reported that an amorphous CD ground mixture instantly changed to its crystalline form when stored at high RH, indicating that the ground mixtures, which produce inclusion compounds in solution, may give inclusion crystals by absorbing water vapor.…”
Section: Solid‐state Cd–drug Interactions Under High Humidity Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amorphous CD–drug complexes usually form when solid complex powders are prepared by cogrinding, spray drying, and freeze‐drying . Typically, amorphous pharmaceuticals exhibit greater molecular mobility and chemical reactivity than their corresponding crystalline forms, giving rise to their lower stability compared with crystalline state . Nakai et al reported that an amorphous CD ground mixture instantly changed to its crystalline form when stored at high RH, indicating that the ground mixtures, which produce inclusion compounds in solution, may give inclusion crystals by absorbing water vapor.…”
Section: Solid‐state Cd–drug Interactions Under High Humidity Conditionsmentioning
confidence: 99%
“…67,70,71 Typically, amorphous pharmaceuticals exhibit greater molecular mobility and chemical reactivity than their corresponding crystalline forms, giving rise to their lower stability compared with crystalline state. 72,73 Nakai et al 47,74 reported that an amorphous CD ground mixture instantly changed to its crystalline form when stored at high RH, indicating that the ground mixtures, which produce inclusion compounds in solution, may give inclusion crystals by absorbing water vapor. In contrast, mixtures containing no inclusion compound may crystallize into their respective component crystals.…”
Section: Solid-state Cd-drug Interactions Under High Humidity Conditionsmentioning
confidence: 99%
“…Among the conventional methods, milling is widely used to prepare the amorphous form of drugs is milling, where the crystalline drug is milled into small-sized amorphous forms, a shortcoming of the milling method. Recently, intraoral delivery formulations were prepared in the amorphous form to exploit the fast dissolution afforded by the metastable amorphous form in the form of either an amorphous solid dispersion [11,84] or cyclodextrin inclusion complex [84][85][86]. Despite shortcomings such as complicated processes, high energy consumptions, high costs, supercritical conditions, and low success rates of the production methods mentioned above, most of the drug formulations created to improve the solubility of insoluble drugs share a common trait their low drug payloads [87][88][89][90].…”
Section: Amorphous Drug-electrolyte Nanoparticle Complexmentioning
confidence: 99%
“…To improve its oral bioavailability, PPZ dosage formulations exhibiting enhanced dissolution have been developed recently by means of salt formulation [199] and amorphization [208]. Alternatively, several studies have proposed the sublingual and buccal delivery routes, in place of the oral route, to enhance the PPZ bioavailability by avoiding the first-pass hepatic metabolism [11,84,86,209,210]. For the intraoral delivery to be effective, fast dissolution of PPZ in the aqueous environment of the oral cavity is also needed, because otherwise the drug would be vulnerable to clearance by swallowing [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation